Hereditary ovarian cancer - Kh. B. Kotiv; T. V. Gorodnova; A. P. Sokolenko; I. V. Berlev; E. N. Imyanitov (Сибирский онкологический журнал, 2022)
Background. Hereditary genetic mutations are a significant risk factor for malignant transformation of cells and cancer development. Hereditary genetic mutations account for 15 to 25 % of all ovarian carcinomas. Purpose of the study: to summarize data on hereditary ovarian malignancies, namely: genetic defects, features of the clinical course, treatment options, and disease prevention. Material and methods. A systemic search was undertaken using PubMed, Medline, Cochrane Library databases for publications from 1999 to 2021. Results. The review describes the main genetic defects and hereditary cancer syndromes predisposing to the development of hereditary malignant ovarian tumors. The features of the clinical course and response to drug therapy have been presented. This article summarizes clinical guidelines of the professional communities (National Comprehensive Cancer Network (NCCN), American Society Of Clinical Oncology (ASCO), The U.S. Preventive Services Task Force, and European Society For Medical Oncology (ESMO). These guidelines contain early detection strategies and approaches to prevent the development of cancers in mutation carriers. Conclusion. Detection of hereditary cancer syndromes is important for patients and their families. Recognizing hereditary predisposition to cancer is important to allow timely surveillance and preventative interventions for both patients and family members.